ANALISIS PEREKAT CAMPURAN SIKAFLEX-EPOXY TERHADAP KEKUATAN TARIK GESER PADA SINGLE LAP JOINT ALUMINIUM DENGAN VARIASI SURFACE PATTERN - Dullah, Muhammad Firdaus Ubai; Hastuti, Sri; Salahudin, Xander (ELEMEN : JURNAL TEKNIK MESIN, 2024)
Vehicle construction requires strong joints to connect various materials. Many connections are made by welding, riveting, and adhesive bonding. Adhesive bonding has the advantages of efficiency, corrosion resistance, and ease of application. This research aims to analyze the effect of using sikaflex (SK) - epoxy (EP) mixed adhesive on the shear tensile strength of single lap joint aluminum. The material used was aluminum 5083 and sika flex and epoxy adhesives with an adhesive thickness of 0.4 mm, as well as variations in surface pattern treatment. The results showed that the highest tensile strength and modulus of elasticity in the variation of 10% SK: 90% EP with surface pattern 90º cross-type amounted to 2.34 MPa and 79.29 MPa. The highest strain was in the variation of 30% SK and 70% EP composition with a 0º horizontal surface pattern of 0.0466. The failure modes that occur are cohesive failure and thin-layer cohesive failure.